Risk factors for peritonitis among Continuous Ambulatory Peritoneal Dialysis (CAPD) patients during training periods - Sulaiman, Nur Shahirah; Ramli, Norazsida; Seman, Mohd Ramli (2017)
Peritonitis is a common complication in patients that undergoing continuous ambulatory peritoneal dialysis (CAPD). This problem causes a major difficulty in performing CAPD treatment efficiently and successfully; especially with the patients that develop this problem at the early stage of training period. Hence, this study was conducted to measure the prevalence of peritonitis during training period among CAPD patients in HTAA and to determine the risk factors associated with peritonitis during training period among CAPD patients in HTAA. This study was conducted by reviewing hospital records. It was conducted as a retrospective study in CAPD unit, Department of Nephrology, Hospital Tengku Ampuan Afzan (HTAA), Kuantan. The inclusion criteria for this study included of all peritonitis patients that undergoing CAPD treatment aged 18 years old and above which develops the complication during training period. The data was chosen along five years duration starting from 1st 2011 to December 31st 2016. The transferred patients that had their Tenckhoff insertion and CAPD training in other hospital were excluded. A total of 65 adult patients were included in the analysis with mean age of 51.58 ± 13.77 year old comprising 32 male (49.2%), 33 female (50.8%), 58 Malays (89.2%), 5 Chinese (7.7%) and 2 Indians (3.1%). Throughout the 5 years, 12 patients were found developed peritonitis during training period (18.5%). Out of these 12 patients, there were7 male (58.3%), 5 female (41.7%), 3 with diabetic (25%), 2 had peritonitis before starting the training and 7 of them (58.3%) had normal body mass index (BMI). Besides, 9 of them were handled by nephrologist for Tenckhoff insertion. History of peritonitis before training was found to be a significant risk factor for the prevalence of peritonitis during training (χ2 (1, n = 65) = 9.114, p = .003, phi = .374). Data analysis also showed that BMI (χ2 (1, n = 65) = 2.379, p = .498, phi = .191), ethnicity (χ2 (1, n = 65) = 1.776, p = .411, phi = .165), gender (χ2 (1, n = 65) = .488, p = .485, phi = .087), person-in-charge for Tenckhoff insertion (χ2 (1, n = 65) = 1.961, p = .161, phi = .174) and diabetes condition (χ2 (1, n = 65) = .514, p = .473, phi = -.089) were not associated with the occurrence of peritonitis during training statistically. In conclusion, patient who develops peritonitis before training also have a high risk of having peritonitis during training. BMI, ethnicity, person-in-charge for Tenckhoff insertion and diabetes condition are found to be not associated with peritonitis. Thus, more factors involving management of the CAPD centre during training should be studied since there were still a few incidence of peritonitis occurred under their monitoring.